2016
DOI: 10.1016/j.celrep.2016.02.086
|View full text |Cite
|
Sign up to set email alerts
|

Aldose Reductase Acts as a Selective Derepressor of PPARγ and the Retinoic Acid Receptor

Abstract: Summary Histone deacetylase 3 (HDAC3), a chromatin modifying enzyme, requires association with the deacetylase containing domain (DAD) of the nuclear receptor co-repressors NCOR1 and SMRT for its stability and activity. Here we show that aldose reductase (AR), the rate-limiting enzyme of the polyol pathway, competes with HDAC3 to bind the NCOR1/SMRT DAD. Increased AR expression leads to HDAC3 degradation followed by increased PPARγ signaling resulting in lipid accumulation in the heart. AR also downregulates e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 92 publications
(109 reference statements)
1
18
0
Order By: Relevance
“…Of note, HDAC3 requires binding to the DAD domain of either NCOR1 or SMRT for its enzymatic function, indicating that NCOR1 regulates recruitment as well as the activity of HDAC3. The importance of NCOR1‐HDAC3 interactions for the regulation of cellular function has been reported in many biological processes including development, metabolism, and glucocorticoid receptor signaling . Apart from HDAC3, NCOR1 can also interact with class II HDACs (HDAC 4, 5, 7) as well as with HDAC1 in combination with the Sin3 repressor complex, thus broadening the spectrum of HDACs recruited to NCOR1 target genes.…”
Section: Basic Facts About Ncor1mentioning
confidence: 99%
“…Of note, HDAC3 requires binding to the DAD domain of either NCOR1 or SMRT for its enzymatic function, indicating that NCOR1 regulates recruitment as well as the activity of HDAC3. The importance of NCOR1‐HDAC3 interactions for the regulation of cellular function has been reported in many biological processes including development, metabolism, and glucocorticoid receptor signaling . Apart from HDAC3, NCOR1 can also interact with class II HDACs (HDAC 4, 5, 7) as well as with HDAC1 in combination with the Sin3 repressor complex, thus broadening the spectrum of HDACs recruited to NCOR1 target genes.…”
Section: Basic Facts About Ncor1mentioning
confidence: 99%
“…In our recent study [181], we showed that the interaction of polyol pathway enzyme aldose reductase (AR) with the nuclear corepressors, NCOR1 and SMRT, could lead to HDAC3 degradration (Figure 2). HDAC3, a class I enzyme exists as a multiprotein complex including HDAC3, nuclear corepressors and cofactors.…”
Section: Novel Mechanisms Impacting Hdac Functionmentioning
confidence: 99%
“…HDAC3 binds to the deacetylation domain (DAD) of either silencing mediator of retinoic and thyroid receptor (SMRT) or nuclear corepressor 1 (NCOR1) [176, 182]. Molecular, cellular, and in vivo studies revealed that AR interaction with the DAD domain of nuclear corepressors drives HDAC3 degradation, consequently leading to the expression of nuclear corepressor’s cofactors including Gps2 , Tblr1 , PPARγ activation and lipid accumulation in the hearts [181]. Our studies demonstrated that regulating the levels of nuclear corepressors or its cofactors could also result in changes of HDACs and consequently transcription.…”
Section: Novel Mechanisms Impacting Hdac Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rev-erbα gene regulates the circadian rhythm to bind site in the BMAL1 gene promoter. The expression of BMAL1 protein is negatively correlated with the mRNA level of Rev-erbα [14][15]. On the other hand, HDAC3 activity contributes to ischemic cardiac damage [16].…”
Section: Introductionmentioning
confidence: 99%